Analysis of Students' Mathematical Literacy on Contextual Problem Viewed from Gender - Yusuf Arkham Prihandika; St Budi Waluya; Nuriana Rachmani Dewi (International Conference on Science, Education, and Technology, 2022)
Abstrak. The mathematical literacy ability is crucial for the students to have in the mathematical study. The purpose of this study is to find out how a student's mathematical literacy ability is reviewed from gender. It falls into a sort of descriptive qualitative research. Subject is chosen using an impressive sampling technique. The data collection techniques used in this research are tests and interviews. To obtain validity data on research used triangulated techniques. The data analysis techniques used in this study are data reduction, data presentation, and deduction drawing. The results of this study show that students' mathematical literacy ability in solving contextual problems between men and women has almost the same characteristics. Male and female students can only achieve indicators of formulating problems and using mathematics to solve problems. This is also the basis for why literacy in Indonesia is low. Lack of motivation and monotonous learning models can also be the cause of low mathematical literacy.